De l’écrit éphémère à l’acte pérenne ? Remarques sur le processus de la mise par écrit au xie siècle aux confins du Dunois et du Chartrain - Chantal Senséby (Bulletin du Centre d’Études Médiévales d’Auxerre)
This article examines five original charters issued by the monks of Marmoutier (France, Indre-et-Loire) between 1064 and 1072 and relating to the church of Dangeau and the land of Sonville (Eure-et-Loir) located in frontier : one charter and four « narrative notices ». One of them is a brief document without notification and it appears as a Vorurkunden or a note. Through an analysis of their external and internal forms and through a study of the context, this paper focus on the various ways of instrumentation and it clarifies their very complex textual links. It stresses the formal diversity and hierarchy of the charters which are deliberate and it testifies a perception and conception of charters which can be changed. Moreover, the five documents are an instrument of power : the priory of Dangeau, recently founded, represent a way to exercise influence over the local population and surrounding area.